Technical Suitability Analysis of Enviromental NGO in Reforestation Activities - La Ode Muhammad Rabiali; Ricky Avenzora; Sofjan Syaf (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
The greening movement initiated by Neo Goverment Organisation (NGO) is considered not capable of providing optimal and sustainable environmental improvements. Though their growth in Indonesia continues to increase (in 2000 years the number reached 13.400) accompanied by large funding in the form of grants from state, private and or donor agencies; especially related to reforestation activities. To this end, this research is conducted to analyze the technical suitability of enviromental NGO in reforestation activities on conformity aspects; location, material, and time. However, these 3 aspects are one of the main factors determining the success of plant life. The study was conducted on environmental NGO in 3 different regions (Yogyakarta, Kolaka District and Muna). Data collection using closed questionnaire (close ended quetionnaire) with scoring system. To interpret each value, a temporary phenomenology approach is used to see how different views of each stakeholders are used Kruskall Wallis analysis. The results of the elitist findings indicate that the technical suitability of environmental NGO in reforestation activities is poor (score 2) both in terms of site suitability, material and time. Keywords: Technical suitability, environmental NGO, greening